Morphine Antinociception Restored by Use of Methadone in the Morphine-Resistant Inflammatory Pain State - Watanabe, Chizuko; Komiyama, Asami; Yoshizumi, Masaru; Sakurada, Shinobu; Mizoguchi, Hirokazu (Frontiers in Pharmacology, 2020)
Antinociceptive effect of methadone in morphine-resistant inflammatory pain state was described in the paw-withdrawal test using the complete Freund’s adjuvant (CFA)-induced mouse inflammatory pain model. After the i.pl. injection of CFA, thermal hyperalgesia was observed in ipsilateral paw. The antinociceptive effects of morphine, fentanyl and oxycodone injected s.c. against thermal hyperalgesia in inflammatory pain state were reduced in ipsilateral paw at 7 days after the CFA pretreatment. On the contrary, the antinociceptive effect of methadone injected s.c. was maintained in ipsilateral paw at 7 days after the CFA pretreatment. The suppressed morphine antinociception in the CFA model mice was bilaterally restored by the s.c.-treatment of methadone at 20 min prior or 3 days after the CFA-pretreatment. The suppressed morphine antinociception was also bilaterally restored by the i.p.-treatment of MK-801 at 30 min prior the CFA-pretreatment, however the s.c.-treatment of morphine at 30 min prior the CFA-pretreatment failed to restore the suppressed morphine antinociception in the CFA model mice. The expression level of mRNA for μ-opioid receptors at 7 days after the i.pl.-pretreatment was not significantly changed by the i.pl.-pretreatment of CFA or s.c.-pretreatment of methadone. In conclusion, the methadone is extremely effective against the thermal hyperalgesia on the morphine-resistant inflammatory pain state, and restores the suppressed morphine antinociception on the inflammatory pain state without altering the expression level of mRNA for μ-opioid receptors.